Naturally Occurring Endocrine Disorders in Non-Human Primates: A Comprehensive Review - Jaco Bakker; Melissa A. de la Garza (Animals, 2022)
Literature concerning veterinary medicine of non-human primates is continuously updated, yet endocrine disorders remain underreported. While case or survey reports of individual endocrinopathies are available, a comprehensive review is not. An exhaustive literature search on this subject via widely used academic search systems, (e.g., Google Scholar, PubMed, BioOne complete and Web of Science), and peer-reviewed publications, proceedings, and newsletters was performed. Selected major endocrine entities will be described with emphasis on clinical signs, morphologic appearances, concomitant diseases, as well as available treatment options. Mostly, no clinical signs were noted and on gross pathology, the endocrine organs were unremarkable. An endocrine-related diagnosis was frequently made as an incidental finding after standard histopathological examination. During the review, the pancreas represented the most affected endocrine organ and diabetes mellitus represented the most clinically significant disorder. Currently, no standard procedure for diagnosing, monitoring, or treating endocrine disorders in non-human primates exists.